Monetary Policy and Governance, Commodity Price Volatility and Tax Revenues in SubSaharan Afric - BASSONGUI, Nassibou (My University, 2023)
This paper investigates the mitigating role of monetary policy and governance in the tax revenue effects of commodity price volatility (CPV) in sub-Saharan Africa. We propose a dynamic panel threshold regression to take into account both the nonlinearity in the relationship between tax revenues and CPV and the endogeneity issues. The estimations show that CPV hurt tax revenues only in the high regime of CPV. Thus, a one-standarddeviation increase in CPV significantly reduces sub-Saharan Africa tax revenues. We also show that low-interest rate, better credits to the economy, and better control of corruption mitigate the detrimental effects of CPV. Sub-Saharan African policymakers should promote accommodative monetary policies, nonconventional monetary policies, and good political governance to tackle the detrimental effects of CPV.
Keywords: commodity price volatility; tax revenues; monetary policy; governance